Individual effects of the copia and gypsy enhancer and insulator on chromatin marks, eRNA synthesis, and binding of insulator proteins in transfected genetic constructs. - Fedoseeva, D.M.; Kretova, O.V.; Gorbacheva, M.A.; Tchurikov, N.A. (Gene, 2018)
Enhancers and insulators are involved in the regulation of gene expression, but the basic underlying mechanisms of action of these elements are unknown. We analyzed the individual effects of the enhancer and the insulator from Drosophila mobile elements copia [enh(copia)] and gypsy using transfected genetic constructs in S2 cells. This system excludes the influence of genomic cis regulatory elements. The enhancer-induced synthesis of 350-1050-nt-long enhancer RNAs (eRNAs) and H3K4me3 and H3K18ac marks, mainly in the region located about 300bp downstream of the enhancer. Insertion of the insulator between the enhancer and the promoter reduced these effects. We also observed the binding of dCTCF to the enhancer and to gypsy insulator. Our data indicate that a single gypsy insulator interacts with both the enhancer and the promoter, while two copies of the gypsy insulator preferentially interact with each other. Our results suggest the formation of chromatin loops that are shaped by the enhancer and the insulator.